Variable area, constant force shock absorption motivated by traumatic brain injury prevention. (6th July 2020) - Fanton, Michael; Alizadeh, Hossein Vahid; Domel, August G; Devlin, Matthew; Kurt, Mehmet; Mungal, M Godfrey; Camarillo, David B; Hawkes, Elliot
Abstract: Compact and efficient energy absorption is desirable for numerous applications including manufacturing, transportation, and protective equipment. An ideal shock absorber is a smart material or structure that can adapt its force-displacement properties to minimize the peak impact force regardless of the impact energy. While traditional shock absorbers can produce precisely-tuned ideal force profiles, they are rigid devices that only compress half of their total length, limiting utility in space-constrained applications. Energy absorbers that are soft and collapsible, such as foams, do not have ideal force profiles and generally have insufficient viscoelasticity to adapt to different impact energies. Here, we present a smart structure concept–variable area shock absorption (VASA)–that leverages a changing contact area in a hydraulically damped collapsible system to passively adapt the force to the minimum necessary to absorb the energy of an impact. Using an analytical fluid dynamics model, we derived the contact area as a function of compression to produce a constant force over the entire stroke of a fixed-orifice damper, and validate this concept experimentally using a preliminary 3D-printed prototype. The VASA prototype follows the constant force profile with a NRMSE between 0.02–0.25 at impact speeds between 2.3 and 4.3 m s −1 . This new approach for absorbing energy is compatible with full collapse of the absorber, enabling soft devices for space-constrained applications in future work. Potential applications include helmets that must absorb energy at a near-minimum force level across multiple impact energy levels.